Evaluation of antifungal activity of “green” Solidago canadensis extracts - Yavorska, H.V.; Vorobets, N.M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
The flowering aerial parts of the local invasive Solidago canadensis were collected in the vicinity of Lviv (Western Ukraine) during flowering in July and August 2024, leaves and inflorescences were separated and dried. Total polyphenols from crushed raw materials were extracted with distilled water, 20 %, 60 %, and 96 % aquatic ethanol solution under reflux condition and maceration. The content of total polyphenols in extracts was determined with a Folin–Ciocalteu reagent and with gallic acid as standard by spectrophotometric method. The strains of unicellular fungi have been used from the Microbial Culture Collection of Ivan Franko National University of Lviv, and method of diffusion in agar for anticandidal investigation. The purpose of the work was to analyze the antifungal activity of green extracts of leaves and inflorescences of S. canadensis, obtained by maceration and reflux methods. The most important results were obtained for aquatic-ethanol extracts. For all extracts obtained from aerial parts of S. canadensis were find a high content of total polyphenols (TPC): in leaves from 3.54±0.04 to 8.55±0.003 mg•g-1 of dry weight (DW) in gallic acid equivalent (GAE) depend on extragent and method of extraction; in inflorescences extracts TPC ranged from 4.15 to 17.35 mg•g-1 DW in GAE. Leaf extracts prepared with aqueous ethanol concentrations of 20%, 60% and 96% showed a zone of growth inhibition (ZGR) of fungi of 7.3–28.0 mm. Extracts of infloresceces had antifungal activity against investigated strains and diameter of ZGR ranged from 8.3 to 31.0 mm. Strong correlations have been found between the ZGR of the fungi Kluyveromyces marxianus, Cutaneotrichosporon curvatus, Candida parapsilosis and the content of polyphenols in the studied extracts. The activity of S. canadensis leaf and inflorescences extracts that we found will contribute to further more detailed study of their properties as antifungal.